Free-standing Sandwich Structure MoO3-rGO Composite Film Electrode for Flexible Supercapacitors. (2019) - Yu, Le; Zhao, Shixi; Wu, Qilong; Zheng, Xiaoxiao; Wang, Yifeng; Wei, Guodan
ABSTRACT: The research of high-performance flexible supercapacitors is urgent due to the rapid development of wearable and portable electronics. The key challenge is the preparation of flexible electrodes with high areal capacitance since electrodes are the most important part of supercapacitors. Compared to those conventional electrodes loading with typical flexible substrates such as textile, PET, paper et al, free-standing electrodes have many advantages such as more efficient capacity contribution, solidly embedded active materials and thinner thickness. Herein, we have successfully fabricated a novel sandwich-like structure free-standing MoO3 -rGO (reduced graphene oxide) composite film electrode for flexible supercapacitors using simple vacuum filtration method followed by HI reduction process. The obtained MoO3 -rGO composite film electrode shows excellent electrochemical performance, whose areal specific capacitance reaches 8972 mF·cm -2 (1.5 mA·cm -2 ). Here, MoO3 provides pseudocapacitance and rGO provides double-layer capacitance. After cycling for 2000 cycles, the capacity retention is 86.7%, showing good cycle stability. Besides, the as-prepared composite film has good flexibility and will not break easily during following bending, rolling, folding or twisting steps. This study has been approved to be an important step for the high-performance electrode design for free-standing flexible supercapacitors.